Theoretical determination of the microstructure of Cs covering of Mo in negative ion sources for nuclear fusion applications. (16th February 2015) - Damone, A; Panarese, A; Coppola, C M; Jansky, J; Coletti, C; Chiodo, L; Serianni, G; Antoni, V; Longo, S
Abstract: Cs is the most well known catalyst used in negative ion sources for fast neutral beam generation employed in nuclear fusion, where the element is evaporated and deposited on Mo surfaces forming non permanent films. In this paper the interaction of Cs with Mo under conditions of interest for negative ion sources is studied using different methods. Cs–Mo potential has been characterized starting from high level electronic calculations for two atoms. Mo–Mo and Mo–Cs potentials are based on new fits of the literature data. Density functional theory calculations on a reduced cell are used to determine the adsorption energy of Cs on Mo for different sites. Good reproduction of experimental results, when available, is achieved (e.g. Mo crystal data, Cs2 dissociation energy) and new results for the evaporation energy of Cs from Mo surfaces, CsMo dissociation energy, adatom geometry etc. are reported and tabulated. A functional expression of the Cs–Mo[0 0 1] interaction potential is proposed based on these ab-initio results. The use of this potential is illustrated by classical MD calculations for the morphology for Cs partial layers on Mo[0 0 1]. Calculations show that the interaction between Cs and the surface leads to peculiar morphology of Cs partial layers, to be considered in future studies of Cs role in negative ion sources as well as in the ongoing quest to alternative catalyzers.